USE OF ANTIPROTOZOAL THERAPY IN HIV INFECTION WITH INTESTINAL PARASITOSIS (Ustozlar uchun, 2026)
Intestinal parasites and helminths cause immunodeficiency in the human body, which directly aggravates the course of the disease in HIV-infected people. The purpose of the study: to study the effect of parasitotherapy on the course of the disease when HIV infection is accompanied by intestinal parasites. Research materials and methods. 70 patients undergoing treatment for HIV infection were examined. General clinical, IFA, PCR, coproovoscopy and formalin sedimentation methods were used for the research.